Geographical analysis of the disabled population and their impact in the city of Amara the community - الساعدي, Dr. Wisam A. Dargal (Journal of College of Education, 2024)
The phenomenon of disability is one of the social problems that spread in societies where there are many wars, the spread of diseases, and the deterioration of the economic, health and social reality, especially in Arab societies. This phenomenon has serious repercussions and negative consequences not only for the disabled, but also for the family and society alike.The research aims to reveal the phenomenon of disability in the city of Al-Amara during the year (2022), and to know the demographic, economic and social characteristics of the disabled population. The research was based on the field study and reached several results, the most important of which is the increase in the number of disabled individuals in the age group under nine years by (38.7%), the number of families (5-8) individuals, the decrease in the level of income by (57.3%), and the increase in The illiteracy rate is )68%(, the availability of suitable housing is )52.3%(, and their job opportunities are reduced by )32%(. The research also showed a number of reasons that contributed to the rise in the phenomenon of disability, and knowledge of the most important economic, health and social impacts on the disabled.
Keywords: Social Welfare, Disabled population, Disability, the society.